The Trypillia in the historiosophy of Yury Lypa - Kucherenko, Svitlana (V. N. Karazin Kharkiv National University Bulletin History of Ukraine. Ukrainian Studies: Historical and Philosophical Sciences, 2022)
The purpose of the article. Elucidation of the views of the Ukrainian publicist, historiographer, geopolitician Yury Lypa (1900–1944) on Trypil archaeological culture, which were formed mainly under the influence of the Ukrainian archaeologist, ethnologist, and art critic Vadym Shcherbakivskyi (1876–1957).The research methodology involves the application of the principles of critical analysis and comparison.Scientific novelty. Borrowings and innovations regarding the interpretation of Tryplian archaeological culture in Lypov historiosophy are taken into account. Yuri Lypaʼs reasoning regarding the significance of the culture of painted ceramics in the ethnogenesis, character, traditions, even in the forms of social organization and political actions of Ukrainians, as well as the social significance of the results of Trypilian researches, is clarified. The Tripoli component of Yuri Lypaʼs concept in his book «The Destiny of Ukraine» (1938) is singled out, the relevant terms and concepts used in the concept are identified and interpreted. The conclusions of modern Tripille studies are given incidentally.Conclusions. The proposed article is one of the attempts to answer the question: Was Yuri Lypa a scientist or a creator of a national myth?